2007
DOI: 10.3168/jds.s0022-0302(07)71548-5
|View full text |Cite
|
Sign up to set email alerts
|

Production Effects of Pathogens Causing Bovine Leukosis, Bovine Viral Diarrhea, Paratuberculosis, and Neosporosis

Abstract: The primary purpose of this research was to determine associations among seropositivity for bovine leukemia virus (BLV), bovine viral diarrhea virus (BVDV), Mycobacterium avium ssp. paratuberculosis (MAP), and Neospora caninum (NC) and each of 3 outcome variables (305-d milk, fat, and protein production) in Canadian dairy cattle. Serum samples from up to 30 randomly selected cows from 342 herds on monthly milk testing were tested for antibodies against BLV (IDEXX ELISA; IDEXX Corporation, Westbrook, ME), MAP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
4
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 29 publications
2
59
4
12
Order By: Relevance
“…In fact, the economic consequences of these two items have been estimated to account for nearly 70% of overall direct economic losses occurring in MAP infections (Ott et al, 1999;Groenendaal et al, 2002). Consistent results regarding the relationship between lower milk yields and PTB are easily found in the literature (Buergelt & Duncan, 1978;Ott et al, 1999;Kudahl et al, 2004;Hendrick et al, 2005;Tiwari et al, 2007;Smith et al, 2009;Aly et al, 2010). In addition to this, some researchers have suggested that PTB is associated with increased mortality rates, higher infertility rates (Merkal et al, 1975;Buergelt & Duncan, 1978;Johnson-Ifearulundu et al, 1999), greater susceptibility to other secondary pathologies such as mastitis (Buergelt & Duncan, 1978) and decreased slaughter value.…”
Section: Introductionsupporting
confidence: 64%
“…In fact, the economic consequences of these two items have been estimated to account for nearly 70% of overall direct economic losses occurring in MAP infections (Ott et al, 1999;Groenendaal et al, 2002). Consistent results regarding the relationship between lower milk yields and PTB are easily found in the literature (Buergelt & Duncan, 1978;Ott et al, 1999;Kudahl et al, 2004;Hendrick et al, 2005;Tiwari et al, 2007;Smith et al, 2009;Aly et al, 2010). In addition to this, some researchers have suggested that PTB is associated with increased mortality rates, higher infertility rates (Merkal et al, 1975;Buergelt & Duncan, 1978;Johnson-Ifearulundu et al, 1999), greater susceptibility to other secondary pathologies such as mastitis (Buergelt & Duncan, 1978) and decreased slaughter value.…”
Section: Introductionsupporting
confidence: 64%
“…Furthermore, other percentages of milk production losses were also described, such as 2.7% reported by Ott, Johnson and Wells (2003), or 3.5% found by Brenner et al (1989). In opposite, some studies have shown that BLV infection has no influence on milk production (KALE et al, 2007;TIWARI et al, 2007) and also in others, BLVpositive cows have even shown an increase in milk production (JACOBS et al, 1991;POLLARI et al, 1992). …”
Section: Discussionmentioning
confidence: 99%
“…There are several studies analysing the effects of MAP infection on the milk yield of dairy cows where a decrease in milk yield is reported (Benedictus et al, 1987;Wilson et al, 1993;Nordlund et al, 1996). The decrease in the milk production of subclinically infected cows tends to be progressive, but statistical differences may only be confirmed in the fourth or later lactations (Tiwari et al, 2007(Tiwari et al, , 2008. However, other authors did not find any difference (Johnson et al, 2001) or even reported an increased milk yield (McNab et al, 1991) in MAP-infected cows.…”
Section: Discussionmentioning
confidence: 99%